Microscopic versus endoscopic stapes surgery: systematic review and meta-analysis. Issue 11 (11th November 2022) - Hajiioannou, J; Gkrinia, E; Tzimkas-Dakis, K; Palla, E; Brotis, A; Korais, C; Saratziotis, A; Lachanas, V; Skoulakis, C
Abstract: Objective: To compare the efficacy and safety characteristics of endoscopic and microscopic stapes surgery based on current evidence. Methods: A systematic literature search was conducted of three medical databases, focusing on randomised, controlled studies or observational studies. Data related to the efficacy and safety of each technique were extracted. Outcome data were summarised using the pooled mean differences or pooled odds ratios, along with their 95 per cent confidence intervals. Results: Thirteen studies were included in the meta-analysis. Success rate was evaluated by estimating air–bone gap improvement; this revealed comparable outcomes for the two techniques (mean difference = −0.20; 95 per cent confidence interval = −0.53, 0.14). No statistically significant difference was detected concerning post-operative complications, except for dysgeusia (odds ratio = −1.12; 95 per cent confidence interval = −1.97, −0.28) and pain (odds ratio = −2.00; 95 per cent confidence interval = −2.97, −1.04), which favoured the endoscopic approach. Conclusion: Though both techniques result in commensurate outcomes concerning success rate, post-operative pain and dysgeusia favour the endoscopic approach. Further high-quality studies are needed to adequately compare the two methods.